(3MOjK GdEac ef GdefXhQ GdEYdGej (B/s - (3QThGf, Ydj eMehOs ((3GdbGgQI (B:s (3GfJQfGSjhfGd HQS ,s, 1994)
(3GdLOjO aj gPG GdcJGH gh Gf GdcJGH jLjH Yf cKjQ ef GdCSFdI efgG Ydi SHjd GdeKGd ? eG gh MOjK GdEac? (B* (3gd MOjK GdEac eLQO LGfH ef GdSjQI GdfHhjI abW (B. (3Ge Gfg LGfH LOjQ HhVYg ehVY GdJMdjd GdYdej HCSdhH eHSW Je GdJhUd Gdi OQhS GYdGejI ? eGgj OhGaY gPG GdMOjK cTGFYI jWdbgG GdGYdGe GdeVGO? eGgj ehGba TNUjGJ gPG GdMOjK? eGgh ehba GdQCj GdYGe GdESdGej ef GdMOjK? eGgj NWhQI GdMQH GdOYGFjI h GdMQH GdfaSjI aj MOjK GdEac? cja YQV GdbQGf MOjK GdEac HGYdi eSJhi ef GdMjGO h GdehVhYjI? cja GcOJ GjGJ MOjK GdEac GdJOab GdeQMdj ddeYdheGJ GdbQGfjI? eG gj GdCSGdjH GdbQGfjI GdEbfGYjI (B. (3dJj GSJNOeJ dEKHGJ Rja TGFYI GdEac? (B*(3cja GYJHQ MOjK GdEac fbWI GfWdGb deYGdLI GdefcQGJ GdEYdGejI(B...(3GdNs
(3HjHdjhZQGajG(B:(3U(B.145-149s
Keywords: (3GdEacs; (3GdOjf GdESdGejs; (3GdEYdGes; (3GdTGFYI GdEYdGejIs